Analysis of ethanol and butanol direct-injection spark-ignition sprays using two-phase structured laser illumination planar imaging droplet sizing. (July 2019) - Koegl, Matthias; Mishra, Yogeshwar Nath; Storch, Michael; Conrad, Chris; Berrocal, Edouard; Will, Stefan; Zigan, Lars
This paper reports on the spray structure of the biofuels, ethanol, and butanol generated by a multihole direct-injection spark-ignition injector, which is studied in a constant volume chamber. The spray shape and structure are analyzed using two-phase structured laser illumination planar imaging where both laser-induced fluorescence and Mie-scattering light are recorded simultaneously for the extraction of instantaneous laser-induced fluorescence/Mie-scattering ratio images. Quantitative planar measurements of the droplet Sauter mean diameter are conducted, using calibration data from phase-Doppler anemometry. The resulting Sauter mean diameters are presented for ethanol and butanol at various fuel temperatures at different times after the start of injection. It is found that an increase in fuel temperature results in a faster atomization and higher evaporation rate, which leads to reduced spray tip penetration and smaller droplet Sauter mean diameter. At equivalent conditions, butanol consistently showed larger spray tip penetration in comparison to ethanol. This behavior is due to the higher surface tension and viscosity of butanol resulting in the formation of larger droplets and larger Sauter mean diameters in the whole spray region. Finally, the butanol injection also shows larger cyclic variations in the spray shape from injection to injection which is explained by the internal nozzle flow that is influenced by larger fuel viscosity as well. The Sauter mean diameter distribution is also compared to phase-Doppler anemometry data showing good agreement and an uncertainty analysis of the structured laser illumination planar imaging-laser-induced fluorescence/Mie-scattering technique for planar droplet sizing in direct-injection spark-ignition sprays is presented.